Network Ties’ Governance in Entrepreneurial Networking of SMEs: Cases of The Owner Managers in The Southern Region of Malaysia - Omar, Siti Sarah; Higgs, Malcolm; Chan, Shiau Wei; Ali, Muazam (Penerbit Universiti Sains Malaysia, 2020)
There were inconsistent findings on the network ties’ governance on the strength of relationship thus supporting the need to empirically prove the variations associated with the elements of entrepreneurial networking. This study aims to explore how the ownermanagers decide the network governance of network ties strength in their relationships in entrepreneurial networking. Specifically, the objective of the study is to determine the governance of network tie strength in entrepreneurial networking. This is a qualitative study involving eight cases of small-sized food manufacturing firms in the southern region of Malaysia using an in-depth interview technique with the owner-managers. The triangulation of data has been carried out by interviewing individuals who are seen as strong and weak ties of the network. This study found that the strength of ties was not only based on the strong intimacy and high emotional attachment (SIHEA) and trust, but also governed by the tie’s human capital (knowledge, skills, experiences, networking); their attitudes and values that dominate the contents of network relationships. It also found that these themes are integrated among each other in entrepreneurial networking. This study adds value to both network and human capital literature. Only few research studies have examined the network ties among small and medium-sized enterprises (SMEs) in Malaysia.